2005
DOI: 10.1093/humrep/deh684
|View full text |Cite
|
Sign up to set email alerts
|

Influence of global sperm DNA methylation on IVF results

Abstract: DNA methylation level in human sperm could represent a new approach to study the ability of sperm to lead to pregnancy in an assisted reproduction procedure, especially when sperm samples with normal characteristics are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 22 publications
11
150
2
3
Order By: Relevance
“…In any case, according to the clinical data at our disposal, our results coincide with the four studies published to date, 19,22,25,47 in which no evidence was found that these anomalies affect the results of assisted reproduction treatments.…”
Section: -supporting
confidence: 89%
“…In any case, according to the clinical data at our disposal, our results coincide with the four studies published to date, 19,22,25,47 in which no evidence was found that these anomalies affect the results of assisted reproduction treatments.…”
Section: -supporting
confidence: 89%
“…DNA methylation has been speculated for many years to have a close association with reproduction and fertility. Benchaib et al (2005) attempted to determine the relationship between sperm DNA methylation level and fertilization and pregnancy rates. It was found that DNA methylation level in human sperm could represent a new approach to study the ability of sperm to lead to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…De novo methylation is known to occur during germ cell maturation and spermatogenesis and this creates hypomethylated regions in the male germ line that are associated with promoters; especially sperm-specific promoter regions that are associated with germ cell functions at distinct stages of spermiogenesis (Houshdaran et al, 2007). With the use of immunostaining, the connection between DNA methylation and fertility was attempted, however, no association was found between sperm DNA methylation and fertilization rate or embryo quality (Benchaib et al, 2005). Houshdaran et al (2007) suggest that if erasing the initial methylation pattern in epigenetic reprogramming does not occur correctly, that there is a possibility of epigenetic defects in the sperm that would ultimately affect male fertility.…”
Section: Methylome Of Sperm Dnamentioning
confidence: 99%
“…However, very little is known about how sperm processing can affect the cells' epigenetic status. One landmark study demonstrated a relationship between differential levels of sperm DNA methylation and IVF outcomes [114]; a later study reported correlations between sperm DNA methylation and semen quality, based on standard assessment criteria including concentration, morphology, and motility [115].…”
Section: A Dilemma For Ivf?mentioning
confidence: 99%